Pendekatan Eksistensial Humanistik Untuk Menurunkan Prilaku Bullying - Ginting, Siska Astria Br; Arsini, Yenti; Tarigan, Sofie Ahmira Rehgita Br (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Bullying is a form of bullying against peers by someone (a child) who is "inferior" or weaker with certain benefits or satisfaction. Bullying usually happens repeatedly. Some are even systematically similar. During the expansion, residence - cases of bullying in educational institutions, especially in school environments, the author takes topics related to bullying in schools at the educational level. The existential-humanistic approach focuses on the nature of the human condition which includes the ability to be self-aware, free to choose to determine one's own destiny, freedom and responsibility, anxiety as a basic element, the search for unique meaning in a meaningless world, being alone and existing. in relationships with others finitude and death, and the tendency to self-actualize. This research aims to describe the application of a humanistic existential counseling approach in reducing bullying behavior in students. This type of research is literature study research where the researcher selects several journals and books where each journal is analyzed and then put together.